2021
DOI: 10.1080/00038628.2021.1921689
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of online teaching in architecture courses

Abstract: In recent decades there has been an increase in online learning in many disciplines including architecture. In 2020, this situation accelerated as architecture programs world-wide transitioned to online learning. This paper uses surveys and semi-structured interviews to evaluate the effectiveness of online teaching for architecture courses. A total of 15 courses from three Australian universities were included in this study, survey results from 88 students in these courses were collected, and three in-depth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…In majors like architecture, research has shown that online studio design should be adopted by schools of architecture as online feedback is a needed skill for architects [ 64 ]. Several online technologies for architecture online programs may be adopted: synchronous sessions mostly delivered via Blackboard Collaborate Ultra which allows drawing overlays on top of the students’ work, or asynchronous sessions via ePinup, a private social networking tool that allows students to upload images of their work and receive comments from peers [ 64 ]. Such tools are not supported at the institution under study and institutions had to pivot to online teaching without any preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…In majors like architecture, research has shown that online studio design should be adopted by schools of architecture as online feedback is a needed skill for architects [ 64 ]. Several online technologies for architecture online programs may be adopted: synchronous sessions mostly delivered via Blackboard Collaborate Ultra which allows drawing overlays on top of the students’ work, or asynchronous sessions via ePinup, a private social networking tool that allows students to upload images of their work and receive comments from peers [ 64 ]. Such tools are not supported at the institution under study and institutions had to pivot to online teaching without any preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, more recently, attention has increasingly focused on students' perceptions of the effectiveness of online design studios, and some studies showed positive effects (Jones et al, 2021; Yu et al, 2021). For example, Yu et al (2021) found that architecture students perceived their online design studios positively due to the increased flexibility. A large‐scale longitudinal study with 3000 students conducted by Jones et al (2021) also showed that online studios were positively correlated with student success in the early stage of the study, although their motivation and success became weaker in the later stage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, more recently, attention has increasingly focused on students' perceptions of the effectiveness of online design studios, and some studies showed positive effects (Jones et al, 2021; Yu et al, 2021). For example, Yu et al (2021) found that architecture students perceived their online design studios positively due to the increased flexibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The agility of students to move between FTF and online learning in which there are no FTF components has been observed (Fleischman, 2019, 2020; Iranmanesh & Onur, 2021; Yu et al ., 2021). Although students have communicated a collective resistance to online studio teaching and a clear level of frustration around changing studio culture, recent studies do not indicate any significant negative impact on the quality of assessable design studio submissions (Yu et al ., 2021). Discussion around the agility of tutors, however, has been more limited.…”
Section: Introductionmentioning
confidence: 99%
“…It is these social characteristics of design studio that contribute to educators’ resistance to online design studio (Bender & Vredevoogd, 2006; Park, 2011; Wood, 2018; Fleischman, 2019) — yet in a time when our real‐world experience is so radically altered and our social conventions re‐thought, it follows that the way we teach and learn in architectural design studio must also change to ensure the ongoing relevance of the studio to contemporary experience. Several studies across architecture (Iranmanesh & Onur, 2021; Yu et al ., 2021), design (Marshalsey & Sclater, 2020; Meyer & Norman, 2020), planning and urban design (Mironowicz & Schretzenmayr, 2020) have indicated that a shift towards online studio is not only possible but is desirable to meet the challenges of a complex world, and that studios still relying on past pedagogies may no longer align with the real‐world complexities of design.…”
Section: Introductionmentioning
confidence: 99%